Triple‐Decker Sandwich Cultures of Intestinal Organoids for Long‐Term Live Imaging, Uniform Perturbation, and Statistical Sampling. Issue 1 (14th January 2022) - Cambra, Hailey M.; Tallapragada, Naren P.; Mannam, Prabhath; Breault, David T.; Klein, Allon M.
Abstract: Three‐dimensional organoid cultures enable the study of stem cell and tissue biology ex vivo, providing improved access to cells for perturbation and live imaging. Typically, organoids are grown in hydrogel domes that are simple to prepare but that lead to non‐uniform tissue growth and viability. We recently developed a simple alternative culture method to embed intestinal organoids in multilayered hydrogels, called "triple‐decker sandwiches, " that align organoids in a common z‐plane with uniform access to medium. This culture configuration improves the growth and survival of organoids over a wide working area and facilitates long‐term confocal imaging and molecular perturbation. Here, we present protocols for preparing organoids in triple‐decker sandwich cultures and using them for live imaging, immunostaining, and single‐cell RNA sequencing. We have tested our methods on mouse and human intestinal organoids and expect them to be useful for other highly proliferative three‐dimensional cell cultures. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Pre‐coating plates with PolyHEMA to prepare them for triple‐decker sandwich culture Support Protocol 1 : Preparing PolyHEMA solution to coat glass‐bottom dishes Basic Protocol 2 : Embedding intestinal organoids in triple‐decker sandwiches Alternate Protocol 1 : Seeding single cells or organoids at low density in triple‐decker sandwiches Support Protocol 2 : Embedding intestinal organoids in hydrogel domes Support Protocol 3 : Production of Wnt3a‐conditioned medium Support Protocol 4 : Production of Rspo1‐conditioned medium Basic Protocol 3 : Live imaging of mouse intestinal organoids in triple‐decker sandwich cultures Alternate Protocol 2 : Live imaging of vital dye–treated mouse intestinal organoids in triple‐decker sandwich cultures Basic Protocol 4 : Immunofluorescence imaging of mouse organoids liberated from triple‐decker sandwich cultures Alternate Protocol 3 : Liberating and fixing mouse intestinal organoids from dome cultures Support Protocol 5 : Measuring cell proliferation by EdU staining of mouse intestinal organoids Basic Protocol 5 : Single‐cell RNA sequencing and analysis of mouse intestinal organoids